FLORIDA INVADER: Tegu Lizards - Steve A. Johnson; Monica E. McGarrity (EDIS, 2011)
Sightings of this large black-and-white invasive lizard, established in areas southeast of Tampa and south of Miami, should be reported immediately to 1-888-IveGot1 or www.IveGot1.org. This 2-page fact sheet, written by Steve Johnson and Monica McGarrity provides pictures and information to aid identification. Published by the UF Department of Wildlife Ecology and Conservation, October 2010.